Sequential Therapy With JX-594, A Targeted Oncolytic Poxvirus, Followed by Sorafenib in Hepatocellular Carcinoma: Preclinical and Clinical Demonstration of Combination Efficacy - Heo, Jeong (Nature Publishing Group, 2011)
JX-594 is a targeted and granulocyte-macrophage colony stimulating factor (GM-CSF) expressing oncolytic poxvirus designed to selectively replicate in and destroy cancer cells through viral oncolysis and tumor-specific immunity. In a phase 1 trial, JX-594 injection into hepatocellular carcinoma (HCC) was well-tolerated and associated with viral replication, decreased tumor perfusion, and tumor necrosis. We hypothesized that JX-594 and sorafenib, a small molecule inhibitor of B-raf and vascular endothelial growth factor receptor (VEGFR) approved for HCC, would have clinical benefit in combination given their demonstrated efficacy in HCC patients and their complementary mechanisms-of-action. HCC cell lines were uniformly sensitive to JX-594. Anti-raf kinase effects of concurrent sorafenib inhibited JX-594 replication in vitro, whereas sequential therapy was superior to either agent alone in murine tumor models. We therefore explored pilot safety and efficacy of JX-594 followed by sorafenib in three HCC patients. In all three patients, sequential treatment was (i) well-tolerated, (ii) associated with significantly decreased tumor perfusion, and (iii) associated with objective tumor responses (Choi criteria; up to 100% necrosis). HCC historical control patients on sorafenib alone at the same institutions had no objective tumor responses (0 of 15). Treatment of HCC with JX-594 followed by sorafenib has antitumoral activity, and JX-594 may sensitize tumors to subsequent therapy with VEGF/VEGFR inhibitors.